Features of Drug Treatment of Acute Community-Acquired Pneumonia in Children with Autonomic Imbalance and Significant Astenic Syndrome - S.L. Nyankovsky; M.S. Yatsula; I.V. Babik; O.I. Shpychka; L.O. Movyak (Zaslavsky O.Yu., 2012)
The article deals with features of clinical course, intensity of toxic, astenic syndrome, vegetative support of children over 7 years old with clinical picture of acute community-acquired pneumonia. Inclusion of probiotic preparation Stimol and metabolic drug Enterol in children's therapeutic regimen leads to faster normalization of clinical, instrumental and functional indices, reduction of autonomic dysfunction manifestations.